Sperm Chromatin Immaturity Observed in Short Abstinence Ejaculates Affects DNA Integrity and Longevity In Vitro - Uppangala, Shubhashree; Mathai, Sherine Eliza; Salian, Sujith Raj; Kumar, Dayanidhi; Singh, Vikram Jeet; D’Souza, Fiona; Kalthur, Guruprasad; Kamath, Asha; Adiga, Satish Kumar (PLOS ONE, 2016)
Background The influence of ejaculatory abstinence (EA) on semen parameters and subsequent reproductive outcome is still debatable; hence understanding the impact of EA on sperm structural and functional integrity may provide a valuable information on predicting successful clinical outcome. Objective To understand the influence of EA on sperm chromatin maturity, integrity, longevity and global methylation status. Methods This experimental prospective study included 76 ejaculates from 19 healthy volunteers who provided ejaculates after observing 1, 3, 5 and 7 days of abstinence. Sperm chromatin maturity, DNA integrity and global methylation status were assessed in the neat ejaculate. Sperm motility, DNA integrity and longevity were assessed in the processed fraction of the fresh and frozen-thawed ejaculates to determine their association with the length of EA. Results Spermatozoa from 1 day ejaculatory abstinence (EA-1) displayed significantly higher level of sperm chromatin immaturity in comparison to EA-3 (P < 0.05) and EA-5 (P < 0.01) whereas; the number of 5-methyl cytosine immunostained spermatozoa did not vary significantly across groups. On the other hand, in vitro incubation of processed ejaculate from EA-1 resulted in approximately 20 and 40 fold increase in the DNA fragmented spermatozoa at the end of 6 and 24h respectively (P < 0.01–0.001). Conclusion Use of short-term EA for therapeutic fertilization would be a clinically valuable strategy to improve the DNA quality. However, use of such spermatozoa after prolonged incubation in vitro should be avoided as it can carry a substantial risk of transmitting DNA fragmentation to the oocytes.